Produksi Hijauan dan Komposisi Botanis di Padang Penggembalaan Alam Desa Ujung Baru Kecamatan Tanasitolo Kabupaten Wajo - Sema (Universitas Islam Negeri Alauddin Makassar, 2023)
The research objective was to determine forage production and botanical composition in natural grazing in Ujung Baru Village, Tanasitolo District, Wajo Regency. This research method uses a descriptive analysis method that describes the condition of the pasture. Measurement of botanical composition using the